Gas Plasma Technology Augments Ovalbumin Immunogenicity and OT‐II T Cell Activation Conferring Tumor Protection in Mice. Issue 10 (8th March 2021) - Clemen, Ramona; Freund, Eric; Mrochen, Daniel; Miebach, Lea; Schmidt, Anke; Rauch, Bernhard H.; Lackmann, Jan‐Wilm; Martens, Ulrike; Wende, Kristian; Lalk, Michael; Delcea, Mihaela; Bröker, Barbara M.; et al.
Abstract: Reactive oxygen species (ROS/RNS) are produced during inflammation and elicit protein modifications, but the immunological consequences are largely unknown. Gas plasma technology capable of generating an unmatched variety of ROS/RNS is deployed to mimic inflammation and study the significance of ROS/RNS modifications using the model protein chicken ovalbumin (Ova vs oxOva). Dynamic light scattering and circular dichroism spectroscopy reveal structural modifications in oxOva compared to Ova. T cells from Ova‐specific OT‐II but not from C57BL/6 or SKH‐1 wild type mice presents enhanced activation after Ova addition. OxOva exacerbates this activation when administered ex vivo or in vivo, along with an increased interferon‐gamma production, a known anti‐melanoma agent. OxOva vaccination of wild type mice followed by inoculation of syngeneic B16F10 Ova‐expressing melanoma cells shows enhanced T cell number and activation, decreased tumor burden, and elevated numbers of antigen‐presenting cells when compared to their Ova‐vaccinated counterparts. Analysis of oxOva using mass spectrometry identifies three hot spots regions rich in oxidative modifications that are associated with the increased T cell activation. Using Ova as a model protein, the findings suggest an immunomodulating role of multi‐ROS/RNS modifications that may spur novel research lines in inflammation research and for vaccination strategies in oncology. Abstract : Successful vaccination requires increased immunogenicity of antigens. Cold physical plasmas produce reactive oxygen and nitrogen species capable of eliciting oxidative protein modifications. Oxidation of ovalbumin (Ova) shows enhanced T cell activation, elevated numbers of antigen‐presenting cells, and decreases tumor burden in vivo upon vaccination.